POLITIK KEBIJAKAN AGAMA DALAM MASYARAKAT PLURAL: MEMBANGUN KERUKUNAN UMAT BERAGAMA MELALUI PANCASILA - Steven; Purba, Gomgom (JURNAL TABGHA, 2024)
Abstract This study discusses the importance of religious policy in creating harmony between religious communities in the context of plural society in Indonesia. As a country rich in cultural, ethnic, and religious diversity, Indonesia faces significant challenges in maintaining social harmony. Although the 1945 Constitution guarantees freedom of religion, the implementation of policies often does not provide fair treatment, especially for minority groups. Through a qualitative approach that relies on literature reviews, statistical data, and interviews with stakeholders, this study highlights the importance of the role of Pancasila as the foundation of the state in building harmony. Pancasila contains universal values ​​that encourage respect for differences and the need to create inclusive and fair policies. This study also identifies challenges in the implementation of religious policies, including the emergence of discrimination and resistance from certain groups. It is emphasized that interfaith dialogue and education on harmony are very important in fostering a tolerant attitude. In order to achieve this goal, collaboration between the government, religious institutions, and civil society needs to be strengthened. Overall, the results of the study show that through fair policies and active community participation, a harmonious environment can be created, where every individual is valued and recognized regardless of religious background